The Anterior Piriform Cortex and Predator Odor Responses: Modulation by Inhibitory Circuits - Matsukawa, Mutsumi; Yoshikawa, Masaaki; Katsuyama, Narumi; Aizawa, Shin; Sato, Takaaki (Frontiers in Behavioral Neuroscience, 2022)
Rodents acquire more information from the sense of smell than humans because they have a nearly four-fold greater variety of olfactory receptors. They use olfactory information not only for obtaining food, but also for detecting environmental dangers. Predator-derived odor compounds provoke instinctive fear and stress reactions in animals. Inbred lines of experimental animals react in an innate stereotypical manner to predators even without prior exposure. Predator odors have also been used in models of various neuropsychiatric disorders, including post-traumatic stress disorder following a life-threatening event. Although several brain regions have been reported to be involved in predator odor-induced stress responses, in this mini review, we focus on the functional role of inhibitory neural circuits, especially in the anterior piriform cortex. We also discuss the changes in these neural circuits following innate reactions to odor exposure. Furthermore, based on the three types of modulation of the stress response observed by our group using the synthetic fox odorant 2,5-dihydro-2,4,5-trimethylthiazoline, we describe how the anterior piriform cortex interacts with other brain regions to regulate the stress response. Finally, we discuss the potential therapeutic application of odors in the treatment of stress-related disorders. A clearer understanding of the odor–stress response is needed to allow targeted modulation of the monoaminergic system and of the intracerebral inhibitory networks. It would be improved the quality of life of those who have stress-related conditions.